Level of Satisfaction in Internet Access as a Source of Information for Grade 11 Humanities and Social Sciences Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The development of the internet in the 21st century has created new informational resources.However, students may readily access the internet connection. Since the internet is regardedas a vast informational resource, internet websites are crucial to our research and can serveas a tool for academic needs. The internet is helpful for quickly finding information andassisting students with their academic work, with just one search on the desired searchengine. Nowadays, students choose to conduct online searches to get information. Theinformation on the internet is easy to understand, beneficial, and believable. The use ofcredible internet resources is of greater importance. The internet may also be used as aresource to study the most recent news from around the globe and to obtain any kind ofinformation for a variety of purposes.The researchers found that students are more satisfied with accessing the internet in terms ofacademic requirements and research sources.The study also revealed that students were "Highly satisfied" with the information they gotfrom the internet. Internet access helps them finish their coursework easily. The researchersrecommend practicing not being satisfied with one piece of information but rather searchingfor another source for comparison and checking reliability. Navigate needed information fromdifferent sources, and always check the review and ratings of a website and the context of theinformation. Always do fact-checking before gathering information.
Keywords: Education